2008
DOI: 10.1051/0004-6361:200809361
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray and optical study of the ultracompact X-ray binary A 1246-58

Abstract: Results are discussed of an X-ray and optical observation campaign of the low-mass X-ray binary A 1246-58 performed with instruments on Satellite per Astronomia X ("BeppoSAX"), the Rossi X-ray Timing Explorer (RXTE), the X-ray Multi-mirror Mission ("XMM-Newton"), the Swift mission, and the Very Large Telescope. Spectra and flux time histories are studied. The most important results are the lack of hydrogen spectral features in the optical spectrum, supporting the proposition that this is an ultracompact X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…On the other hand, similar features have been observed in several (candidate) UCXBs (e.g. Juett et al 2001;Juett & Chakrabarty 2003;Farinelli et al 2003;in 't Zand et al 2008). These are proposed to result from over-abundances in the absorbing material, generally enhanced O, Ne and Fe, which is probably intrinsic to the sources.…”
Section: Analysis and Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…On the other hand, similar features have been observed in several (candidate) UCXBs (e.g. Juett et al 2001;Juett & Chakrabarty 2003;Farinelli et al 2003;in 't Zand et al 2008). These are proposed to result from over-abundances in the absorbing material, generally enhanced O, Ne and Fe, which is probably intrinsic to the sources.…”
Section: Analysis and Resultssupporting
confidence: 78%
“…In addition, optical spectroscopic studies have been used to test the ultra-compact nature of several systems. This is done by investigating the absence/presence of emission/absorption features in the spectra, which provide hints on the chemical composition of the accreted material, and thus, on the nature of the compan- ion star (Nelemans et al 2004(Nelemans et al , 2006in 't Zand et al 2008;Hernández Santisteban et al 2017). Likewise, X-ray spectroscopy has been used to search for UCXB candidates.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the properties of the X‐ray burst of J1735 are very similar to the intermediately long bursts from XTE J1701−407 (Falanga et al 2009; Linares et al 2009) and 4U 1246−58 (in't Zand et al 2008), which both triggered the BAT and were subsequently observed by the XRT. The three X‐ray bursts have similar BAT rise times of tens of seconds, and we found that the XRT tails show comparable decay rates.…”
Section: Discussionmentioning
confidence: 53%
“…Several intermediately long X‐ray bursts have been detected from (candidate) ultracompact X‐ray binaries (UCXBs; see e.g. in't Zand et al 2005, 2008; Falanga et al 2008; Kuulkers et al 2009). These systems have orbital periods ≲80 min, which implies that the donor star must be H deficient (Nelson, Rappaport & Joss 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation